THE MINIATURE OF GOD AND THE TERMINOLOGY OF THE BIBLE TEXT FROM THE ISLAM PERSPECTIVE - Nopriyansa, Eko (Jurnal Diskursus Islam, 2020)
The characteristic of a religion never been far from the textual influence of a holy book as its absolut fundamental. The religious figures of  accross time seemed to have given a tremendous effect to the religions itself. Moreover, according to the religious research, religions have become a spirit of the civilizations. Most people consider religions as an alternative solution to a political polemic, social dilemma, or conflicts between groups. What is more interesting is that between two religions, they share quite similiar relevance and terminology, but their perspective are substantially different. For one example, the chronicle of Ibrahim, the sacrifical of his son, theological concept terminology, textual suitability and fact-finding science, and some prophets chronicles. Given from the explanations above, it is a responsibility for every people to determine the characteristic of their religions. Therefore, this article is aimed to give an explicit explanation about Islam as the ultimate religion to correct and to complement the previous holy books, particularly to observe the miniature of God within the Holy Bible in Christianity, as well as the the credibility of Islamic expression in the perspective of the Holy Bible.